CHALLENGES AND REGIONAL LEGISLATIVE STRATEGIES IN GUIDING COMMUNITY-BASED DEVELOPMENT: A CASE STUDY IN INDONESIA - Maros, Asra’i; Al Hidayat, Nanang; Sunaryo, Joko (Qawwam : The Leader's Writing, 2025)
Regional legislatures play a crucial role in ensuring that development policies align with the needs of the community. However, within Indonesia’s decentralized governance system, various challenges persist in the legislative process, including weak coordination with the executive branch, low public participation, and limited capacity among legislators to formulate evidence-based policies. This study aims to identify the main challenges faced by legislative bodies in overseeing community-needs-based development and to formulate strategies that can be implemented to improve the effectiveness of regional legislation. This research employs a qualitative approach using a case study method in several regions across Indonesia. Data were collected through in-depth interviews with legislative members, academics, and civil society organizations, and analyzed using thematic analysis techniques. The findings indicate that executive dominance in policy formulation, limited capacity among legislators, and a lack of transparency in the legislative process are the main factors hindering the effectiveness of the legislative role. Recommended strategies include enhancing legislators’ capacity through evidence-based training, strengthening public participation mechanisms through digital platforms, and implementing policy reforms to increase legislative independence in overseeing regional development. The conclusion of this study emphasizes that the success of community-needs-based development depends on the extent to which the legislative body can perform its role transparently, accountably, and participatorily. The results of this research contribute to the literature on local governance and offer practical recommendations for policymakers to improve the effectiveness of regional legislation. Further research is recommended to expand the geographical scope of the study and to explore more deeply the impact of regulations on the implementation of community-needs-based development.